The construction of houses - Dann, Nigel; Marshall, Duncan; Worthing,Derek; heath, Roger (London New York: Routledge, 2013)
"The fifth edition of this successful textbook is aimed specifically at those students and practitioners who require a broad understanding of building construction as part of a wider sphere of professional activity. This book provides a comprehensive introduction to the principles and practice of modern construction and services. In addition most chapters contain information on earlier construction techniques to reflect the age profile of the UK housing stock. This new edition has a revised text and hundreds of revised graphics, new illustrations and photos, and is fully up to date with today's methods. This highly accessible text concentrates on principles and practice rather than details and regulations. In doing so it enables the reader to demonstrate a comprehensive and genuine understanding of modern house construction and its evolution over the last 100 years"--Provided by publisher
Includes index
Keywords: House construction; Dwellings -- -- Design and construction